Mass loss of Greenland's glaciers and ice caps 2003–2008 revealed from ICESat laser altimetry data. Issue 5 (13th March 2013) - Bolch, T.; Sandberg Sørensen, L.; Simonsen, S. B.; Mölg, N.; Machguth, H.; Rastner, P.; Paul, F.
Abstract [1] The recently finalized inventory of Greenland's glaciers and ice caps (GIC) allows for the first time to determine the mass changes of the GIC separately from the ice sheet using space‐borne laser altimetry data. Corrections for firn compaction and density that are based on climatic conditions are applied for the conversion from volume to mass changes. The GIC which are clearly separable from the icesheet (i.e., have a distinct ice divide or no connection) lost 27.9 ± 10.7 Gt a−1 or 0.08 ± 0.03 mm a−1 sea‐level equivalent (SLE) between October 2003 and March 2008. All GIC (including those with strong but hydrologically separable connections) lost 40.9 ± 16.5 Gt a−1 (0.12 ± 0.05 mm a−1 SLE). This is a significant fraction (~14 or 20%) of the reported overall mass loss of Greenland and up to 10% of the estimated contribution from the world's GIC to sea level rise. The loss was highest in southeastern and lowest in northern Greenland.